THU0085 RESOLVIN D5 MODULATES TH17/TREG CELL DIFFERENTIATION AND SUPPRESSES OSTEOCLASTOGENESIS. (2nd June 2020) - Yamada, H.; Saegusa, J.; Sendo, S.; Ueda, Y.; Okano, T.; Fujikawa, Y.; Yamamoto, Y.; Nagamoto, T.; Ichise, Y.; Naka, I.; Akashi, K.; Onishi, A.; et al.
Abstract : Background: Resolution phase of acute inflammation has been recognized not passive but active process during the last 2 decades. This active process is highly regulated by novel families of potent bioactive lipid mediators, which are coined as specialized proresolving mediators (SPMs) including resolvins. Little has been known, however, about how resolvins are involved in chronic inflammation, such as rheumatoid arthritis (RA). Objectives: To investigate whether lipid mediators (LM) are involved in the pathogenesis of RA. Methods: We investigated lipid mediator profiling in the paws of SKG arthritis mice by using lipid chromatography (LC) /mass spectrometry (MS) /MS-based LM metabololipidomics. CD4 + T cells from spleens of SKG mice were cultured on anti-CD3/ CD28Abs precoated plate with IL-6/TGF-β, anti-IFNγ/IL-4 and analyzed by flow cytometry. CD4 + T cells were labeled with CFSE, and cell proliferation was analyzed by flow cytometry. Mouse bone marrow cells were cultured with M-CSF and RANKL, and TRAP-positive multinucleated cells were defined as osteoclasts. Osteoclast differentiation markers were analyzed by qRT-PCR. RvD5 or normal saline was administered daily into the peritoneal cavity of arthritic SKG mice. Results: RvE3, RvD1, RvD3, RvD5 and Maresin2 were significantly elevated on the paws of arthritic SKG mice. Among the elevated SPMs, only RvD5 levels on arthritic paws were significantly correlated with arthritis disease activity (Figure 1). We demonstrated that RvD5 suppressed Th17 cell differentiation, and facilitated Treg cell differentiation in vitro . In addition, RvD5 inhibited CD4 + T cell proliferation. Furthermore, RvD5 attenuated osteoclast differentiation (Figure 2) and interfered osteoclastogenesis at the molecular level. In the in vivo experiment, incidence of arthritis tended to be lower in RvD5-treated mice than that in control group, although there was no significant difference. Conclusion: RvD5 is increased in the paws of arthritic mice, and that RvD5 suppresses Th17 cell differentiation and CD4 + T cell proliferation, facilitates Treg cell differentiation, and suppresses osteoclastogenesis. References: [1]Serhan, C. N. 2014. Pro-resolving lipid mediators are leads for resolution physiology. Nature 510: 92-101. [2]Buckley, C. D., Gilroy, D. W., Serhan, C. N. 2014. Proresolving lipid mediators and mechanisms in the resolution of acute inflammation. Immunity 40: 315-27. [3]Colas, R. A., Shinohara, M., Dalli, J., Chiang, N., Serhan, C. N. 2014. Identification and signature profiles for pro-resolving and inflammatory lipid mediators in human tissue. Am J Physiol Cell Physiol 307: C39-54. Acknowledgments: The authors thank Shino Natsui (Department Rheumatology and Clinical Immunology, Kobe University Graduate School of Medicine) for providing technical assistance. Disclosure of Interests: None declared